The capital gain lock-in effect with short sales constraints - Klein, Peter (Journal of Banking & Finance, 1998)
This paper develops a post-tax asset pricing model under the assumption that investors cannot defer the taxation of capital gains by costlessly short selling tax exempt perfect substitute securities. Contrary to existing literature, it is demonstrated that trading rules of immediate realization of losses and voluntary deferral of gains may not be optimal. Further, equilibrium prices are shown to be higher for stocks held by investors with large accrued capital gains and lower for stocks held by investors with small accrued capital gains or losses.